In-situ thermo-mechanical testing of fly ash geopolymer concretes made with quartz and expanded clay aggregates - Rickard, William; Gluth, G.; Pistol, K. (2016)
The mechanical and microstructural properties of geopolymer concretes were assessed before, during and after high temperature exposure in order to better understand the engineering properties of the material. Fly ash based geopolymer concretes with either quartz aggregate or expanded clay aggregate were exposed to various temperatures up to 750 °C using a thermo-mechanical testing apparatus. Microstructural investigations were also undertaken to better understand the measured changes in the mechanical properties. It was found that dehydration of capillary water caused cracking and strength losses at temperatures ≤ 300 °C, an effect that was more severe in the quartz aggregate geopolymer due to its lower permeability. At higher temperatures (T ≥ 500 °C) sintering promoted strength increases which enabled both concrete types to yield significant strength advantages over conventional materials. Stress–mechanical strain curves, which form the basis of the fire design of concrete structures, are reported.